2019
DOI: 10.1109/tmi.2019.2900516
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Segmentation Using an Open Large-Scale Dataset in 2D Echocardiography

Abstract: Delineation of the cardiac structures from 2D echocardiographic images is a common clinical task to establish a diagnosis. Over the past decades, the automation of this task has been the subject of intense research. In this paper, we evaluate how far the state-of-the-art encoder-decoder deep convolutional neural network methods can go at assessing 2D echocardiographic images, i.e. segmenting cardiac structures as well as estimating clinical indices, on a dataset especially designed to answer this objective. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
306
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 399 publications
(352 citation statements)
references
References 29 publications
(47 reference statements)
7
306
0
3
Order By: Relevance
“…The dataset is composed of apical 4-chamber view images annotated for LV and LA segmentation, with uneven imaging quality from 500 patients with varying conditions. Notably, the initial benchmarking (Leclerc et al, 2019) on this dataset has shown that modern encoder-decoder CNNs resulted in lower error than inter-observer error between human cardiologists. Ghesu et al (2016) proposed a framework based on marginal space learning (MSL), deep neural networks (DNNs) and active shape model (ASM) to segment the aortic valve in 3D cardiac ultrasound volumes.…”
Section: Multi-chamber Segmentationmentioning
confidence: 99%
“…The dataset is composed of apical 4-chamber view images annotated for LV and LA segmentation, with uneven imaging quality from 500 patients with varying conditions. Notably, the initial benchmarking (Leclerc et al, 2019) on this dataset has shown that modern encoder-decoder CNNs resulted in lower error than inter-observer error between human cardiologists. Ghesu et al (2016) proposed a framework based on marginal space learning (MSL), deep neural networks (DNNs) and active shape model (ASM) to segment the aortic valve in 3D cardiac ultrasound volumes.…”
Section: Multi-chamber Segmentationmentioning
confidence: 99%
“…To validate the efficiency of RAL, we built a large multi-view echocardiographic sequences dataset, which was acquired from three centers' various vendor machines (The Second People's Hospital of Shenzhen, The Third People's Hospital of Shenzhen, and Peking University First Hospital). We further evaluate RAL on the public CAMUS dataset [6]. Our dataset contains 300 sequences from 3 views and every sequence includes 30 frames.…”
Section: Methodsmentioning
confidence: 99%
“…The application scenario of existing methods is always limited and only suitable under a specific situation. They mostly focus on specific view [4] or single frames (i.e., without considering the sequence) [5] or one single vendor and center [6]. As for sequence segmentation, existing methods try to leverage temporal information by using a deformable model combined with the optical flow [7,8] or fine-tuning pretrained CNN dynamically with first frame's label till the last frame [9].…”
Section: Gaps Across Views Gaps Across Vendors and Centersmentioning
confidence: 99%
“…The number of feature maps given in table corresponds to the number of convolutions in the convolution layers. For each U-Net implementation, the values for the first, the bottom (where the spatial information is the most compressed), and the last convolution layers indicated (Leclerc et al, 2019).…”
Section: Appendix Amentioning
confidence: 99%
“…There are many suggested methods for 2D LV segmentation. Recently Deep Convolutional Neural Networks have shown promising results for image segmentation (Jafari et al, 2018;Leclerc et al, 2019), specifically U-Net, which has been successfully applied to multiple medical image segmentation problems. As explained in the abstract, this study aims to investigate and compare the performance of U-Net 1 and U-Net 2 models reported by (Leclerc et al, 2019) with the original U-Net (Ronneberger et al, 2015).…”
Section: Introductionmentioning
confidence: 99%